The Fibrosis and Immunological Features of Hypochlorous Acid Induced Mouse Model of Systemic Sclerosis - Meng, Meng; Tan, Jieqiong; Chen, Weilin; Du, Qian; Xie, Bin; Wang, Nian; Zhu, Honglin; Wang, Kangkai (Frontiers in Immunology, 2019)
Fibrotic animal models are critical for the pathogenesis investigations and drug explorations in systemic sclerosis (SSc). The bleomycin (BLM)-induced mouse model is the classical and most widely used fibrosis model. However, traditional subcutaneous injection of BLM rarely induced diffuse skin and lung lesions. Hypochlorous acid (HOCl)-induced mice are a more representative model that have diffuse cutaneous lesions, lung fibrosis and renal involvement. However, the fibrotic and immunological features of this model are not fully elucidated. Here, we injected BALB/c mice subcutaneously with HOCl used at different concentrations of HOCl (1:55, 1:70, and 1:110 NaClO: KH2PO4, hereafter named HOCl55, HOCl70, and HOCl110, respectively) for 6 weeks to induce fibrosis, and also used HOCl110 at different time course (4, 5, and 6 weeks). Morphological changes were observed via HE and Masson's trichrome staining. Immunohistochemistry or real-time PCR was used to detect inflammatory infiltrates, important fibrosis pathways and pro-inflammatory mediator expression. Flow cytometry was used to detect the alteration of immune cells in mouse spleen. Skin and lung fibrosis were most obvious in the HOCl55 group compared to lower concentration groups. In the HOCl110 group, dominant inflammatory infiltrates were found after 5 weeks, and significant fibrosis was found after 6 weeks. Then we explored the fibrosis and immunological profiles in the HOCl110 (6 weeks) group. Important fibrosis pathway proteins such as TGF-β, NF-κB, Smad3, p-Smad3, STAT3, and p-STAT3 were significantly elevated at week 6 in the HOCl110 group. Increased infiltration of CD4+T cells, CD8+T cells, CD20+B cells, and myofibroblasts was found both in skin and lung tissues. However, decreased CD4+T cells, CD8+T cells, monocytes and macrophages and increased CD19+B cells were found in the spleen tissues. The mRNA expression of fibrosis mediators such as IL-1β, IL-6, IL-17, IL-33, TNF-α, and CTGF was also upregulated in skin and lung tissues. In conclusion, HOCl induced fibrosis mouse model displayed systemic immune cell infiltration, pro-inflammatory mediator release, vasculopathy and fibrosis, which better mimicked human SSc than BLM-induced mice.